Reinforcement of metal structures by external reinforcement by gluing high-strength fiber-reinforced systems: analytical approach - Rudneva, Iryna (Transfer of innovative technologies, 2021)
Ukraine's construction heritage includes numerous examples of the use of metal structures, especially those used in industrial buildings and high-span structures. The use of metal structures in construction is due primarily to their mechanical properties. They are frost-resistant and can withstand temperatures down to -65 degrees, hard, durable, strong and reliable. They can also be used in areas with high seismic activity. But, as in the case of other types of structures, there is a need to restore or strengthen metal structures due to structural defects, wear of load-bearing elements, as well as to increase the load-bearing capacity. In some cases, reinforcement with fiber-reinforced polymer composites (FRP) gives a better result compared to traditional methods of reinforcement using metal